Guidance and Best Practices for Nuclear Cardiology Laboratories During the COVID-19 Pandemic: An Information Statement From ASNC and SNMMI. (September 2020) - Skali, Hicham; Murthy, Venkatesh L.; Al-Mallah, Mouaz H.; Bateman, Tim M.; Beanlands, Rob; Better, Nathan; Calnon, Dennis A.; Dilsizian, Vasken; Gimelli, Alessia; Pagnanelli, Robert; Polk, Donna M.; Soman, Prem; et al.
Abstract : Supplemental Digital Content is available in the text.